Cope strategies for victims of sexual violence in adolescents: scoping review - Istiani Yoviana; Tetti Solehati; Dyah Setyorini (Universitas Aisyah Pringsewu, 2023)
Sexual abuse that occurs during adolescence can affect its development in various aspects of life. The stressful situation experienced by the victim has an impact on the physiological, psychological, and social. Individuals will do coping to overcome them. Adolescents often fall into maladaptive coping strategies, causing them to experience depression. This study aims to identify coping strategies for victims of sexual violence in adolescents through literature review. This study uses a scoping review method through searches on the Pubmed database, EBSCOhost, and the Google Scholar search engine using the keywords